Sensitization of Resistance Ovarian Cancer Cells to Cisplatin by Biogenic Synthesized Silver Nanoparticles through p53 Activation - Ramezani, Tayebe (Iran J Pharm Res, 2019)
Today, drug resistance is one of the major problems in fight against cancer. Therefore, combination of therapeutic strategies was raised to effectively improve disease prognosis. In this regard, silver nanoparticles (AgNPs) are considered significant due to their anticancer properties. This study aimed to return sensitivity to cisplatin to A2780 cisplatin-resistance cell lines in the presence of biogenic synthesis curcumin-coated silver nanoparticles (cAgNPs). Synergic cellular effects of cAgNPs and cisplatin on ovarian carcinoma 2780 resistant to cisplatin cells were assessed using MTT assay, Acridine orange (AO)/propidium iodide (PI), DAPI staining, Annexin V/PI assay, and caspase 3/9 activation assay. Finally, expression of p53 and MMP-9 genes were evaluated using semi-quantitative reverse transcription polymerase chain reaction (RT-PCR). According to the results, 8 µg/mL and 62 µg/mL of cAgNPs and cisplatin led to 50% cell death in 48 h, respectively. Therefore, we combined non-toxic concentration of nanoparticles (1-5 µg/mL) with cisplatin (2.5 µg/mL). Decreased proliferation rate was about 50% for synergic use of cisplatin (2.5 µg/mL) and cAgNPs (2 µg/mL). According to the results, cell death induction significantly increased by AO/PI, DAPI staining and Annexin V/PI assay in the combined group. Moreover, activity of caspase 3/9 significantly increased in the mentioned group. The combined use of cAgNPs and cisplatin resulted in upregulated expression of p53 gene and downregulated expression of MPP-9 gene. As observed in this study, a combination of cAgNPs and cisplatin increased the efficiency of apoptosis induction in A2780 cells, compared to the independent use of cisplatin or cAgNPs.